Traditions and Novelty in the Semantic Organization of the Word-Symbol Kalyna (on the material of poetry) - Колесникова, Лариса Леонідівна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”)
The article deals with the semantic organization of the traditional Ukrainian symbol kalyna, which was presented in the poetry. Its folkloric and symbolic meaning was analyzed. In modern poetic structure the weakening of paradigm „kalyna – girl” was noted depending on the lowing the level of anthropomorphic background of poetic text. It was proved that the psychological author’s state much influences on the developing secondary word-symbol kalyna semantics. The following semes were determined, such as ‘desolation of national sources’, ‘artificial extermination of the nationals’, ‘life continuity’, ‘family prolongation’, ‘rebirth’, ‘beauty’.